Career pathways[videorecording] : Two years on - Video Education Australasia (Australia : VEA, 2004)
This program provides a fascinating insight into the realities of career development. It is divided logically into five chapter; education and training, work, family, personal development and advice. The students have all changed in the past two years, both in visible and non-visible ways. All have lessons to share and advice to give.
1. Introduction -- 2. Education and training -- 3. Work -- 4. Family -- 5. Personal development -- 6. Advice
'A great discussion-starter!'
Teacher notes by Peter Krausz
Playbox theatre, John Staley ; Monash university, Justin Meli, Ben Harding ; camera, Richard Leigh ; sound, Wayne Martin ; additional images, British satellite news ; editor, Paul Sutherland ; production manager, Edwina Baden-Powell ; educational consultant, Peter Krausz ; writer/producer/director, Richard Leigh ; commissioning editor, Christine Henderson ; executive producer, Mark McAuliffe
Allan, Bestami, James, Kahli, Reeni, Michelle
Keywords: Career development; Occupations; Vocational guidance